Patient-related determinants of antibiotic use: a systematic review. (January 2019) - Zanichelli, V.; Tebano, G.; Gyssens, I.C.; Vlahović-Palčevski, V.; Monnier, A.A.; Stanic Benic, M.; Harbarth, S.; Hulscher, M.; Pulcini, C.; Huttner, B.D.
Abstract: Objectives: We aimed to assess patient-related determinants potentially influencing antibiotic use. Methods: Studies published in MEDLINE until 30 September 2015 were searched. We included: qualitative studies describing patients' self-reported determinants of antibiotic use; and quantitative studies on either self-reported or objectively assessed determinants associated with antibiotic use. Whenever possible, reported determinants were categorized as 'barriers' or 'facilitators' of responsible antibiotic use. Results: A total of 87 studies from 33 countries were included. Seventy-five (86.2%) were quantitative and described self-reported (45/75, 60.0%), objectively assessed (20/75, 26.7%) or self-reported and objectively assessed (10/75, 13.3%) patient-related determinants. Twelve (12/87, 13.8%) were qualitative studies or had a qualitative and quantitative component. Eighty-six of the studies (98.8%) concerned the outpatient setting. We identified seven broad categories of determinants having an impact on different aspects of antibiotic use (in descending order of frequency): demographic and socio-economic characteristics, patient–doctor interactions (e.g. counselling), treatment characteristics (e.g. administration frequency), attitudes (e.g. expecting antibiotics), access to treatment (e.g. patients' direct costs), characteristics of the condition for which the antibiotic was prescribed (e.g. duration of symptoms), knowledge (e.g. regarding indications for treatment). Most determinants were classified as 'barriers' to responsible antibiotic use. Conclusion: A large variety of patient-related determinants impact antibiotic use. The most easily 'modifiable' determinants concern patient–doctor interactions, treatment characteristics and knowledge. Data from the inpatient setting and low- and middle-income countries were underrepresented. Further studies should develop and test interventions that take these determinants into account with the ultimate aim of improving responsible use of antibiotics.